Fabrication of Hyperuniform Dielectric Networks via Heat‐Induced Shrinkage Reveals a Bandgap at Telecom Wavelengths. Issue 14 (28th June 2022) - Aeby, Stefan; Aubry, Geoffroy J.; Froufe‐Pérez, Luis S.; Scheffold, Frank
Abstract: Recent studies report photonic bandgaps (PBGs) in disordered hyperuniform network structures numerically and experimentally for high enough refractive index contrast. However, the smallest experimental central gap wavelength that one can realize experimentally is not close to the essential near‐infrared light spectrum with adverse consequences for specific applications and more advanced experimental studies. Indeed, standard direct laser writing (DLW) lithography does not allow fabrication at a much higher resolution. Here, the authors demonstrate heat‐treatment induced uniform shrinkage of the network's polymer template obtained by DLW to reach smaller feature sizes and subsequent silicon coating, resulting in a pronounced gap near telecom wavelengths. Abstract : The limited axial resolution of direct laser writing lithography prevents the fabrication of hyperuniform dielectric networks with an optical response at near‐infrared wavelengths. With heat‐treatment induced uniform shrinkage of the network's polymer template, one can improve the effective resolution and reach smaller feature sizes. Subsequent titania and silicon coating result in amorphous photonic materials with a gap near telecom wavelengths.